Building design effect relationship to maintenance / Nadia Kamaruddin - Kamaruddin, Nadia (2008)
Maintenance is important in buildings in order to maximize the life span of building, to reduce the probability of failure in term of performance of the building, to retain value of the property and to make sure a good appearance of the building. Design deficiencies are one of the causes that deterioration occurred. Thus, maintenance aspect should be considered in early stage of building design until the end. This is important to avoid deterioration on building and to avoid problems in maintenance in the future. The objectives of this research are to find out whether the building design does affect the maintenance work on high rise building and to study the problems of maintenance work regarding the design of the building. For the purposes, postal surveys by hundred questionnaires set were distributed to at least 20 buildings in Klang Valley. The feedback from the survey of questionnaires, only 48 questionnaires were returned and answered completely by 16 buildings. Then in depth interviews have been made to the selected 4 out of 16 buildings to discuss further regarding to building design effect to maintenance.